miR-376a Provokes Rectum Adenocarcinoma Via CTC1 Depletion-Induced Telomere Dysfunction - Liu, Yang; Zhao, Xiaotong; Wang, Bing; Liu, Zhijia; Zhang, Manman; Wang, Jinhan; Xu, Chang; Wang, Yan; Du, Liqing; Wang, Feng; Wang, Qin; Liu, Qiang (Frontiers in Cell and Developmental Biology, 2021)
CTC1 is a component of the mammalian CST (CTC1–STN1–TEN1) complex which plays essential roles in resolving replication problems to facilitate telomeric DNA and genomic DNA replication. We previously reported that the depletion of CTC1 leads to stalled replication fork restart defects. Moreover, the mutation in CTC1 caused cancer-prone diseases including Coats plus (CP) or dyskeratosis congenita (DC). To better understand the CTC1 regulatory axis, the microRNAs (miRNAs) targeting to CTC1 were predicted by a bioinformatics tool, and the selected candidates were further confirmed by a dual-luciferase reporter assay. Here, our current results revealed that miR-376a significantly reduced CTC1 expression at the transcription level by recognizing CTC1 3′-UTR. In addition, the overexpression of miR-376a induced telomere replication defection and resulted in direct replicative telomere damage, which could be rescued by adding back CTC1. Telomere shortening was also observed upon miR-376a treatment. Furthermore, for the clinical patient samples, the high expression of miR-376a was associated with the deregulation of CTC1 and a poor outcome for the rectum adenocarcinoma patients. Together, our results uncovered a novel role of miR-376a in stimulating rectum adenocarcinoma progression via CTC1 downregulating induced telomere dysfunction.